2015
DOI: 10.1261/rna.047522.114
|View full text |Cite
|
Sign up to set email alerts
|

Predicting RNA 3D structure using a coarse-grain helix-centered model

Abstract: A 3D model of RNA structure can provide information about its function and regulation that is not possible with just the sequence or secondary structure. Current models suffer from low accuracy and long running times and either neglect or presume knowledge of the long-range interactions which stabilize the tertiary structure. Our coarse-grained, helix-based, tertiary structure model operates with only a few degrees of freedom compared with all-atom models while preserving the ability to sample tertiary structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 41 publications
1
70
0
Order By: Relevance
“…As particular RNA structures are known to affect RBP binding in pre-mRNA splicing (Warf and Berglund, 2010), mRNA decay (Goodarzi et al, 2012), and mRNA localization (Rabani et al, 2008), we classified each RNA base as being part of a stem, hairpin loop, interior loop, or multiloop (Kerpedjiev et al, 2015). Averaging over all 78 proteins, we found that in pulldown sequences, top RBNS 6mers were present in hairpin loops about twice as often as all 6mers and in stems approximately half as often ( Fig.…”
Section: Rna Structural Preferences Of Rbpsmentioning
confidence: 97%
“…As particular RNA structures are known to affect RBP binding in pre-mRNA splicing (Warf and Berglund, 2010), mRNA decay (Goodarzi et al, 2012), and mRNA localization (Rabani et al, 2008), we classified each RNA base as being part of a stem, hairpin loop, interior loop, or multiloop (Kerpedjiev et al, 2015). Averaging over all 78 proteins, we found that in pulldown sequences, top RBNS 6mers were present in hairpin loops about twice as often as all 6mers and in stems approximately half as often ( Fig.…”
Section: Rna Structural Preferences Of Rbpsmentioning
confidence: 97%
“…Characteristics of the hairpin structure were encoded as features using the forgi package 22 . The features used in our algorithm are largely the same as those used in miRanalyzer and listed in Table 3 of the original paper 15 .…”
Section: Methods For Novel Mirna Detectionmentioning
confidence: 99%
“…For example, NAST [51] and YUP [52] represent each nucleotide as a single pseudo atom, Vfold [53], SimRNA [54] and iFoldRNA [55] define each nucleotide using three pseudo atoms, CG [56] represents each nucleotide with five pseudo atoms, and HiRE-RNA [57] uses six pseudo atoms to represent purines and seven for pyrimidines. In addition, there are methods that represent RNA as graphs, which further reduces the sampling space by representing each helix as a stick or a cylinder [58, 59]. The accuracy of coarse-grained methods depends on the choice of representation and the scoring function.…”
Section: Progress and Challenges In Rna 3d Modeling Methodsmentioning
confidence: 99%